A Chatbot that Uses a Multi-agent Organization to Support Collaborative Learning - Colissi, Mateus (2021)
This work investigates and apply the use of a multi-agent system to assist in the coordination of group tasks, specifically in educational environments, in which the interaction occurs indirectly, that is, asynchronously. The system has a web interface integrated with a chatbot for more natural interaction. The chatbot communicates with the multi-agent system that is responsible for the organization of the group, that is, it contains information about the tasks and members of the groups, in addition to restrictions that can be imposed according to the organization of the group, and it is also able to return the requested information in natural language through the chatbot. This approach was validated in a practical undergraduate course of software engineering. The students assessed the functionalities and usability of the system while working in groups in order to develop software collaboratively. Our system was used to assist students in a real project. With this assessment, it was found that the system was able to support the development of the group tasks, ensuring quick and consistent responses to the student’s request.